Engaging Students as Health Cadres in the Implementation of a Healthy Campus - Heni Trisnowati; Aufatcha Ayutya Suryana (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Background: The younger generation has a very important role in determining the success of health development. Efforts to mobilize youth in public health development can be made in the form of participation as health cadres. Universities or campuses as student affairs have a strategic role in creating a healthy and superior young generation. To describe the implementation of student health cadre training as part of healthy campus activities at one of the private universities in Yogyakarta, Indonesia. Methods: Student health cadre training is part of the healthy campus program which was implemented on October 28, 2021, in collaboration with the Public health office dan Public Health Center at Sleman Regency Yogyakarta. Training materials include healthy living skills education, the urgency of student health cadres, and smoke-free area ambassadors. 30 student representatives were invited to attend the training but participation was voluntary. The criteria for training participants are students who are active in student activities and taken purposively. Results: The student health cadre training was carried out as planned and 30 students participated from start to finish. Participants were enthusiastic during the training and at the end of the session it was agreed to create a WhatsApp group as a follow-up to the program. Based on the pre-test and post-test, there was an increase in student knowledge about healthy life skills education from a score 69,67 to 78,67 after training with P value < 0,05. In addition, training participants are committed to helping realize a healthy campus, such as admins on healthy campus social media. Conclusion: Student health cadre training is an important activity in the implementation of a healthy campus. This activity is a form of student involvement as a healthy campus course. Students who have attended the training are expected to be pioneers of peer educators for other students in terms of practicing a healthy lifestyle.